Transitioning towards end-of-life care in Jordanian critical care units: health care professionals' perspectives - Almansour, Issa Mohammad Ali (2015)
This study explored the experiences of Jordanian critical care staff about the transition to, and provision of, end of life care. It examined the difficulties they encountered, and how they sought to care for and communicate with the families of patients who were approaching the end of life. The study took place in two University hospitals in different cities. A mixed methods design in two phases was adopted. The first phase employed the “National Survey of Critical Care Nurses' Perceptions of End-of-Life Care” (adapted with permission) to elicit the views of critical care staff (N=104) about the obstacles and facilitators to providing end of life care for critically ill patients and their families. In the second phase, qualitative interviews were conducted with staff (15 nurses; 10 junior doctors; 5 head nurses).